A GEOCHEMICAL INVESTIGATION OF SOILS, APPLES AND LEAVES IN AGIA AREA, CENTRAL GREECE - Skordas, K.; Papastergios, G.; Filippidis, A.; Kantiranis, N. (Bulletin of the Geological Society of Greece, 2016)
Forty two soil, apple and leaf samples from Agia area, central Greece, were collected and analyzed for their content in 7 major elements (Ca, Fe, K, Mg, Na, NP and S). The average concentration of the determined elements follows the Norder: concentration in soils > concentration in leaves > concentration in apples. Elements, such as Fe that is found enriched in the soils of the study area, due to local geology, is not correlated with its concentrations in apples and leaves, possibly because of its association with resistant minerals. On the other hand, the relationship of some elements (i.e., K, P, S) that are constituents of the agrochemicals applied in the area, indicate that they are more readily available by the trees, either because they are associated with less resistant (clay) minerals, or because they derive through the application of agrochemical products (i.e., phosphate fertilisers, fungicides etc.).